Culture's “In-Betweens”: Diaspora and artistic practice of Gavin Jantjes, Marlene Dumas and Moshekwa Langa. - Speakes, Olga (Michaelis School of Fine Art, 2024)
In 2017, the term “diaspora” is ubiquitous in any form of engagement with contemporary art and artists from Africa. Whether we scroll through the titles of the latest contemporary art exhibitions on the continent and outside, learn about the buzzy new additions to the annual art fair calendar, leaf through the pages of art publications, hear of the new museums of contemporary African art being inaugurated or engage in the theoretical discourse through art history conferences, catalogue essays and scholarly monographs, the talk is no longer about African art or even contemporary African art, but about contemporary art from Africa and its diaspora (s). The term “diaspora” is certainly not new, and originated in the discipline of history and, particularly, in Jewish studies. Its current omnipresence in the fields of art history and theory, however, is the result of a number of new critical, theoretical and curatorial tendencies that have gained particular momentum since the last two decades of the twentieth century.